PERIMETER INTRUSION DETECTIVE SYSTEM USING ARDUINO - Naing, Thiri; Khaing, Kyi Kyi; Nwet, Tin Tin (APTIKOM Journal on Computer Science and Information Technologies, 2019)
Perimeter intrusion detection systems are an integral part of most physical security systems. The mainfocus of the Perimeter Intrusion Detection System (PID) is on the fence intrusion. To secure public and private placessuch as military bases, airports, power station and security related application, the used of perimeter fencing iswidely applicable for isolating and protecting. Fence structures merely prevent a percentage of intrusions orpostpone them. Therefore, to monitor and investigate activities on or around the university, a higher level of securityis needed. The system used major components as Arduino board, 8x8 LED display, ultrasonic sensor, 16x2 LCDdisplay module and speaker. The unauthorized person who tries to intrude the university woulld be sensed, detectedand alarm would generate a signal that an intruder was trying to enter the university. The sound level depended onthe distance, the nearer the intruder and stronger would be the alarm signal. PID system displayed the distance of theobject or personal found in its region on the LCD display. This system was very useful for security applications.Ultrasonic sensor would be searching if there was a motion in its range.